Bioequivalence Evaluation of a Fixed Dose Combination Lamivudine + Stavudine Tablet with Concurrent Administration of Lamivudine Tablet and Stavudine Capsule in Healthy Volunteers - Chachad, Siddarth; Lulla, Amar; Malhotra, Geena; Purandare, Shrinivas (Arzneimittelforschung, 2009)
The study was designed to compare the rate and extent of absorption of a fixed dose combination tablet of lamivudine (CAS 134678舑17舑4) and stavudine (CAS 3056舑17舑5) with the concurrent administration of lamivudine tablet and stavudine capsule in 24 healthy volunteers under fasting conditions. The volunteers were randomly assigned to the test or reference treatment, with the two treatment periods separated by a washout period of at least 7 days. Plasma samples were analyzed for both analytes lamivudine and stavudine by a validated analytical method. Since the 90% confidence intervals for the “test/reference” mean ratio of the Intransformed pharmacokinetic variables Cmax, AUC0–t and AUC0–∞ were clearly within the conventional bioequivalence range of 80% to 125%, the two treatments were considered bioequivalent. The safety profiles of both the test and reference formulations were comparable.
Keywords: Antiretroviral drugs; CAS 3056-17-5; CAS 134678-17-4; Fixed dose combination; Lamivudine, bioequivalence, pharmacokinetics; Stavudine, bioequivalence, pharmacokinetics